Achievements of beet industry of Ukraine in system of the collective farm researching work in 1930th-1950th - Kovalenko, S. D. (History of science and technology, 2018)
The development of beet industry of Ukraine in the times of collective farm researching work (1930th-1950th) was investigated in the article with the method of historical-scientific analysis. It has defended that achievements took place on a collective basis in accordance with the implementation of government decisions, addressed to the rural population. It was found out that activity in collective farms has been carried out at the head of agronomic organizations in the village in the form of houses-laboratories, then houses of agricultural culture and collective farm research stations as leaders of collective research. It has found out that research on agrotechnique of sugar beet cultivation were carried out on the most common soils in the sugar beet regions of Ukraine – chernozems. These scientific researches were carried by the guidance of research institutes and stations on agrotechnique of cultivation, breeding, dynamics of cultivation of sugar beets for ensuring sugar production in Ukraine and solving the feeding problem in livestock breeding. The crop rotations have also introduced - plans for multi-year use of fields and alternation of cultivated plants as an important step towards improving the activity of the beet-breeding industry. Its aimed at fulfilling the main state tasks of growing beets and other crops, ensuring sustainable and rapid increase of yield, creation of a strong forage base for animal breeding, proper use of labor, tractors, livestock and agricultural machinery of a certain collective farm. It has noted the industrialization of the industry that made it possible to equip the beet farms with tractors and other equipment and the wave of the Stakhanov movement in beet production in the middle of the 1930’s. The representation of the achievements in production of beet growing through the constantly-functioning All-Union Agricultural Exhibition and periodicals which represented experience leading figures of agricultural science and practice, news on agrotechnics, mechanization, chemicalization of crops, issues of beet crop rotation, pest control of the crops, organization of labor in beet farms, brigades, houses-laboratories, specific information on training and other problems of collective farms has highlighted. The condition of beet growing in the 1940s-1950s was studied, in particular the influence of the war in 1941-1945 on this branch and its rebuilding.